Exploring the predictors of attrition in the Bepresent universal Self-directed digital parenting program - Koivusaari, Catherine (My University, 2026)
Background: Universal digital self-directed parenting interventions support families by enhancing the quality and consistency of parental practices. The context of this study is the Bepresent parent training program in Finland, which experienced a 64% attrition rate. Attrition poses a significant challenge to the effectiveness and efficacy of interventions. Aims: The objective of the study is to examine how parental, child, and family structure, as well as child behavioral factors and family perceived difficulties, are associated with attrition and completion rates during the intervention. Methods: Data have been extracted from participants in the Bepresent universal, self-directed parent training program. Irritability was measured using the Affective Reactivity Index-Parent Report (ARI-P), hyperactivity, conduct problems, and family perceived difficulties were assessed using the Strengths and Difficulties Questionnaire (SDQ). The outcomes of the study are the attrition rates, which are divided into three completion groups: early dropouts, partial completers, and full completers. The following analysis methods have been employed: (1) Descriptive analysis to summarize participant characteristics and key variables across the three attrition groups, (2) Univariate multinomial logistic regression analysis to examine and summarize each variable individually to understand data distribution and attrition patterns, (3) Multivariate multinomial logistic regression analysis to examine whether the associations remained significant after controlling for other variables. Results: Parents (N=1338) enrolled in the program and completed the preintervention questionnaire. There was an almost even distribution of participants, though the 3 main completion rates and the total sample of full completers were 423. Mothers (n=1186) and biological parents (n=1234) comprised the highest number of participants. Parents of boys had the highest number of full completers (35.1%) and were more likely to be retained in the program than the parents of girls. Child gender (P=.007), participants´ gender (P=.003), family perceived difficulties (P=.002), and hyperactivity (P=.002) were significantly associated with attrition. Family structure (P=.13), irritability (P= .44 and conduct problems (P=.07) were not significantly associated with attrition. Conclusion: Attrition in universal self-directed digital interventions is not random, and results show that attrition is associated with demographics, Parental and child characteristics, as well as child behavioral problems. Recommendations for future research are discussed.
Keywords: Attrition; Behavioral problems; Digital parental training; Parental attritions; Positive parenting; Universal intervention